Advancing Sustainable Construction - Optimizing 3D-Printed Bio Fiber-Based Lightweight Building Elements - Ehrnberg, Herman; WIkström, Simon (My University, 2025)
To address the continuous global population growth with the goal of simplifying the construction of affordable and environmentally friendly living spaces this thesis focuses on the impact of the building materials. In collaboration with an ongo ing research project at Chalmers University of technology on cellulose-based Hybrid Composite Materials used in 3D-printing building elements a user-friendly design tool is created. The tool is created as a Grasshopper component for Rhinoceros 3D with the main goal of simplifying the use of the 3D-printable Hybrid Composite Material for the building sector. It takes its basis in Finite Element Analysis cal culations in combination with Generative Design and Topological Optimisation as well as theory for 3D-Printing. From the research project access to the material as well as the 3D-printer is achieved making the collection of necessary data possible. When finalised, the program is used to showcase a few cases, both as 3-dimensional computer models as well as 3D-printed. At the end of the report the results as well as the different methods are discussed and examples of how to bring the subject even further, improvements for the program, as well as further ideas are debated.
Keywords: Keywords: Hybrid Composite Material, Finite Element Method, Generative Design, Topology Optimisation, Grasshopper, 3D-Printing